DIETA E COMPORTAMENTO DE CAÇA DA CORUJA-BURAQUEIRA (ATHENE CUNICULARIA) NA CIDADE UNIVERSITÁRIA DE DOURADOS, MS, BRASIL - OLIVEIRA, Inessa Steffany Torres de; LOPES, Tatiana de Albuquerque; CORDEIRO, Luiza Vieira; MACHADO, Vinicius de Souza; JUNIOR, Olivio Alves de Melo; CASTRO, SaúriaLúcia Rocha de (ANAIS DO ENIC, 2017)
-